2015
DOI: 10.7554/elife.06516
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic chromosomal restructuring during genome elimination in plants

Abstract: Genome instability is associated with mitotic errors and cancer. This phenomenon can lead to deleterious rearrangements, but also genetic novelty, and many questions regarding its genesis, fate and evolutionary role remain unanswered. Here, we describe extreme chromosomal restructuring during genome elimination, a process resulting from hybridization of Arabidopsis plants expressing different centromere histones H3. Shattered chromosomes are formed from the genome of the haploid inducer, consistent with genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
118
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 38 publications
18
118
0
Order By: Relevance
“…Progenies of the cross (HI X WT) of A. thaliana also yield high frequency of aneuploids along with haploids (Ravi and Chan, 2010). Besides, several structural chromosomal rearrangements giving rise to novel phenotypes have been reported (Tan et al, 2015). Thus, with regard to aneuploids, our results are in agreement with Ravi and Chan (2010) but differ from Kelliher et al (2016) who found no aneuploids in CENH3-based HI lines of maize.…”
Section: Discussionmentioning
confidence: 99%
“…Progenies of the cross (HI X WT) of A. thaliana also yield high frequency of aneuploids along with haploids (Ravi and Chan, 2010). Besides, several structural chromosomal rearrangements giving rise to novel phenotypes have been reported (Tan et al, 2015). Thus, with regard to aneuploids, our results are in agreement with Ravi and Chan (2010) but differ from Kelliher et al (2016) who found no aneuploids in CENH3-based HI lines of maize.…”
Section: Discussionmentioning
confidence: 99%
“…Similar mechanisms of chromosome shattering and re-ligation also appear to be present in genetic plant [38] and fission yeast [39] models of chromosome missegregation. In Arabidopsis models, apparent micronuclei have been reported to produce complex rearrangements [38] that are strikingly similar to chromothripsis observed in human cancer genomes, implicating chromothripsis as a potentially conserved consequence of mitotic errors across evolution.…”
Section: The Micronucleus Revisitedmentioning
confidence: 85%
“…In Arabidopsis models, apparent micronuclei have been reported to produce complex rearrangements [38] that are strikingly similar to chromothripsis observed in human cancer genomes, implicating chromothripsis as a potentially conserved consequence of mitotic errors across evolution. Interestingly and along similar lines, protozoan ciliates such as Tetrahymena carry both a macronucleus and a micronucleus, the latter containing germline chromosomes that undergo deliberate DNA fragmentation and extensive rearrangements for subsequent conversion into the macronucleus [40].…”
Section: The Micronucleus Revisitedmentioning
confidence: 99%
See 2 more Smart Citations